Study of Environmental Impact Analysis with Geospatial Technique in Newtown, Kolkata, India - PAUL, RUPA; PANDIT, ABHIJIT; DEY, SHARADIA; MONDAL, SABYASACHI (The journal of contemporary issues in business and government, 2021)
The expansion in planned pattern occupies the north-eastern fringe of Kolkata by development of New Town area due to development of human settlement. It has led to the rise of temperature along with impervious surface, important in analysing the Urbanization and present day environmental condition. The Geospatial Technique helps in analysing the land use change pattern. It incorporates Landsat8 OLI of 2018,Landsat 7 ETM+ of 2010 satellite data. Software modelling is done followed by interpretation. The Built-up area Index (BI), Land Surface Temperature (LST) Index on temporal and spatial scale can justify the rate of increase in urbanized area along with rise of temperature. Urban Heat Island condition is analysed. It can predict probable impact on future climatic condition of Newtown location in Kolkata.